2022
DOI: 10.1111/1471-0528.17315
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcomes in Italy during COVID‐19 pandemic: A population‐based cohort study

Abstract: Objective To compare the estimates of preterm birth (PTB; 22–36 weeks' gestational age, GA) and stillbirth rates during COVID‐19 pandemic in Italy with those recorded in the three previous years. Design A population‐based cohort study of live‐ and stillborn infants was conducted using data from Regional Health Systems and comparing the pandemic period (1 March 2020–31 March 2021, n = 362 129) to an historical period (January 2017–February 2020, n = 1 117 172). The cohort covered 84.3% of the births in Italy. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 37 publications
(42 reference statements)
2
16
0
Order By: Relevance
“…Our study reveals a significant reduction in rate of preterm delivery (8.7% in COVID-19 lockdown period compared to 13.02% in non COVID 19 period) similar to a study conducted in Italy which also showed a reduced relative risk ratio of preterm births by 0.91 with confidence interval CI (0.88-0.93). 13 This study was similar to a study conducted in Canada in 2020 with a preterm births of 84/1000 live births and 92.7/1000 live births (p=0.007) in COVID-19 and non COVID-19 period respectively. 14 Similarly, another study conducted in Tennessee in 2020 also revealed reduction in preterm births 10.2% and 11.3% in COVID-19 and non COVID-19 period with p value of 0.003 .…”
Section: Discussionsupporting
confidence: 89%
“…Our study reveals a significant reduction in rate of preterm delivery (8.7% in COVID-19 lockdown period compared to 13.02% in non COVID 19 period) similar to a study conducted in Italy which also showed a reduced relative risk ratio of preterm births by 0.91 with confidence interval CI (0.88-0.93). 13 This study was similar to a study conducted in Canada in 2020 with a preterm births of 84/1000 live births and 92.7/1000 live births (p=0.007) in COVID-19 and non COVID-19 period respectively. 14 Similarly, another study conducted in Tennessee in 2020 also revealed reduction in preterm births 10.2% and 11.3% in COVID-19 and non COVID-19 period with p value of 0.003 .…”
Section: Discussionsupporting
confidence: 89%
“…During the second lockdown, the stillbirth rate did not differ compared to the years from 2010 to 2019 [ 26 ]. No increase in the stillbirth rate was also observed in the previously cited Italian study on several regions when comparing the first wave period with previous years (up to 2017) [ 23 ].…”
Section: Discussionsupporting
confidence: 51%
“…There was also an increase, but not a significant one, in very PTB [ 22 ]. Another study, covering 10 Italian regions and based on regional health systems, indicated that the pandemic period (1 March to 31 March 2020) compared with the historical one (January 2017 to February 2020) was associated with a reduced risk for PTB (odds ratio (OR) = 0.90; 95%CI: 0.87–0.93) [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…5 A big cohort study from Italy found no association of COVID-19 on preterm birth or stillbirth rates. 6 The findings from UK and US registries showed increased risk of preterm delivery and maternal mortality, whereas stillbirth, low birthweight and early neonatal death rates were not affected. 7 Reduction in preterm birth rates and elective cesarean section (CS) was observed in Iceland with no change in induction of labor.…”
Section: Introductionmentioning
confidence: 98%